Performance of P16INK4a immunocytochemical stain in facilitating cytology interpretation of HSIL for HPV-positive women aged 50 and above - Hou, Jun; Du, Hui; Wang, Chun; Song, Fangbin; Qu, Xinfeng; Wu, Ruifang (Frontiers in Oncology, 2024)
Background: Few articles had focused on cytological misinterpretation of the highgrade squamous intraepithelial lesion (HSIL). Due to estrogen deficiency, cervical epithelial cells in postmenopausal women tend to show atrophic change that looks like HSIL on Papanicolaou stained cytology slides, resulting in a higher rate of cytological misinterpretation. P16 INK4a immunocytochemical staining (P16-cytology) can effectively differentiate diseased cells from normal atrophic ones with less dependence on cell morphology. Objective: To evaluate the role of P16-cytology in differentiating cytology HSIL from benign atrophy in women aged 50 years and above. Methods: Included in this analysis were women of a cervical cancer screening project conducted in central China who were positive of hr-HPV and returned back for triage with complete data of primary HPV testing, Liquid-based cytology (LBC) analysis, P16 immuno-stained cytology interpretation, and pathology diagnosis. The included patients were grouped by ≥50 (1,127 cases) and < 50 years (1,430 cases) of ages. The accuracy of LBC and P16-cytology in detection of pathology ≥HSIL was compared between the two groups, and the role P16 immuno-stain in differentiating benign cavical lesions from Cytology ≥HSIL was further analyzed. Results: One hundred sixty-seven women (14.8%; 167/1,127) in ≥50 group and 255 (17.8%, 255/1,430) in <50 group were pathologically diagnosed as HSIL(Path-HSIL). LBC (≥ASCUS) and P16-cytology(positive) respectively detected 63.9% (163/255) and 90.2% (230/255) of the Path-≥HSIL cases in <50 group and 74.3% (124/167) and 93.4% (124/167) of the Path-≥HSIL cases in ≥50 group. LBC matched with pathology in 105 (41.2%) of the 255 Path-≥HSIL cases in <50 group and in 93 (55.7%) of the 167 Path-≥HSIL cases in ≥50 group. There were 5 in <50 group and 14 in ≥50 group that were Path-≤LSIL cases, which were interpreted by LBC as HSIL, but negative of P16cytology. Conclusion: P16-cytology facilitates differentiation of Path-≤LSIL from LBC-≥HSIL for women 50 years of age and above. It can be used in the lower-resource areas, where qualified cytologists are insufficient, as the secondary screening test for women aged ≥50 to avoid unnecessary biopsies from misinterpretation of LBC primary or secondary screening.